2021
DOI: 10.29328/journal.cjog.1001092
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Female Genital Mutilation among daughters of reproductive aged women at Academic Charity Teaching Hospital (ACTH)

Abstract: Introduction: It is estimated that more than 200 million girls and women alive today have undergone female genital mutilation. Female genital mutilation still remains to be a serious problem for large proportion of women in most sub-Saharan Africa countries including Sudan, with a high prevalence of 88%. Objective: The main objective was to identify the factors associated with FGM among daughters of reproductive aged woman. Materials and methods: A community based cross-sectional study was conducted on 200 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
2
0
0
Order By: Relevance
“…Daughters whose birth took place at a health facility were found to have a lower likelihood of experiencing genital mutilation compared to daughters born at home. This finding is consistent with a study that conducted hierarchical analysis on factors associated with a daughter's FGM ( 60 ) and as well as studies conducted in Africa ( 67 , 68 ). One possible reason for this association could be that giving birth at a health facility is linked to better access to information, education, and counselling regarding the sexual and reproductive health of both the mother and daughters.…”
Section: Discussionsupporting
confidence: 91%
“…Daughters whose birth took place at a health facility were found to have a lower likelihood of experiencing genital mutilation compared to daughters born at home. This finding is consistent with a study that conducted hierarchical analysis on factors associated with a daughter's FGM ( 60 ) and as well as studies conducted in Africa ( 67 , 68 ). One possible reason for this association could be that giving birth at a health facility is linked to better access to information, education, and counselling regarding the sexual and reproductive health of both the mother and daughters.…”
Section: Discussionsupporting
confidence: 91%
“…Level of education is another factor reported in this study, which was also referred to in research in Sierra Leone, which also indicated that women with a higher level of education had a higher probability of declaring that FGM should be stopped [21]. Likewise, in Sudan, those with primary or higher levels of education were less likely to undergo FGM than those who were illiterate [22]. A study carried out in Egypt, using data from the 2008 DHS, found that the mother's level of education had a positive impact on reducing support for FGM [23].…”
Section: Discussionsupporting
confidence: 76%